1977
DOI: 10.1161/01.res.40.6.584
|View full text |Cite
|
Sign up to set email alerts
|

Maximum rate of tension fall during isometric relaxation at end-systolic fiber length in canine papillary muscle.

Abstract: SUMMARYWe measured the characteristics of the decline in tension during isometric relaxation of canine papillary muscle. In the intact heart, relaxation begins with the isovolumic phase, but in experiments on papillary muscle previously reported the isotonic phase preceded the isometric phase during the course of relaxation. In our experiments, however, the isotonic bar was locked at the instant the muscle reached the end-systolic fiber length in order to hold the fiber at that length during the succeeding rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
16
1

Year Published

1978
1978
1997
1997

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 6 publications
6
16
1
Order By: Relevance
“…There was a highly significant correlation between both parameters as already observed in isolated preparations from other mammalian species (Tamiya et al, 1977;Pery-Man et al, 1993a,b). By contrast, in control and during exposure to TBQ, there was no such correlation between twitch tension and t1/2 (not shown).…”
Section: Resultssupporting
confidence: 73%
See 3 more Smart Citations
“…There was a highly significant correlation between both parameters as already observed in isolated preparations from other mammalian species (Tamiya et al, 1977;Pery-Man et al, 1993a,b). By contrast, in control and during exposure to TBQ, there was no such correlation between twitch tension and t1/2 (not shown).…”
Section: Resultssupporting
confidence: 73%
“…Indeed, the slope of this relationship has been used as an index of the intrinsic relaxing capabilities of the muscle in isometric conditions (Tamiya et al, 1977;PeryMan et al, 1993a,b). Any manoeuvre (application of TBQ or increase in the stimulation frequency) that decreases the slope of this correlation exerts an 'intrinsic' negative relaxant effect.…”
Section: Experimental Protocolmentioning
confidence: 99%
See 2 more Smart Citations
“…In the whole heart, peak -dP/dt, the maximal rate of pressure decline after end ejection, has been applied as an index of myocardial relaxation (13)(14)(15), but its magnitude has been shown to be influenced by developed pressure (14). Similarly, a recent study using isolated papillary muscle applied peak -dT/dt to characterize isometric relaxation and demonstrated that peak -dT/dt is influenced by developed tension (16). In an attempt to normalize peak -dT/dt for the change in tension produced by hypoxia, two additional indices of relaxation were examined: peak -dT/dt divided by the instantaneous tension at which peak -dT/dt occurred, and the maximum value of the continuous division of the rate of tension fall (-dT/dt) by the corresponding instantaneous tension.…”
Section: Discussionmentioning
confidence: 99%